PENGEMBANGAN MEDIA CARD MATCH CIRCLE UNTUK MENINGKATKAN HASIL BELAJAR PANCASILA SISWA KELAS V SEKOLAH DASAR - Muhammad Alamul Amri (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The main objective of this study is to determine the level of effectiveness of the circle match card media on the Pancasila learning outcomes of 5th grade students at Oro-Oro Ombo Kulon II public elementary school, Rembang District, Pasuruan Regency, after conducting a series of learning that has been supported by the development of interactive visual media. This research and development uses RnD (research and Development) and the ADDIE development model, namely analysis, design, development, implementation and evaluation. The place and time of this study began in September to November 2025, with a population of 44 students in the subject of 5th grade at Oro-Oro Ombo Kulon II public elementary school, Rembang, Pasuruan. Research and development on the Pancasila content of the Indonesian cultural diversity material of the independent curriculum. The results of the study show that the development of the Card Match Circle media has improved student learning outcomes. The learning outcomes of students in the experimental class post-test averaged 71.36 and the control class averaged 47.72. The learning outcomes that have been given to students show an increase in the development media that has been implemented. The media that has been developed has met the eligibility requirements with a percentage of 83% by the validators, however, the researcher hopes that subsequent developers can develop it better and more effectively in analyzing needs, creating content, designing designs and allocating learning time appropriately. ABSTRAK Tujuan inti penelitian ini adalah untuk mengetahui tingkat efektfitas media card match circle pada hasil belajar Pancasila peserta didik kelas V di sekolah dasar negeri Oro-Oro Ombo Kulon II Kecamatan Rembang, Kabupaten Pasuruan, setelah melakukan serangkaian pembelajaran yang telah ditunjang dengan pengembangan media visual interaktif. Penelitian dan pengembangan ini menggunakan RnD (research and Development) dan model pengembangan ADDIE, yaiitu analisis, desain, pengembangan, implementasi dan evaluasi. Tempat dan waktu penelitian ini dimulai bulan September hingga November 2025, dengan populasi 44 peserta didik pada subjek kelas V sekolah dasar negeri oro-oro ombo kulon II Rembang,Pasuruan. Penelitian dan pengembangan pada muatan Pancasila materi keragaman budaya indonesiaku kurikulum merdeka. Hasil penelitian menunjukkan bahwa pengembangan media card match circle telah meningkatkan hasil belajar peserta didik. Hasil belajar peserta didik pada kelas eksperimen uji post-test rata-rata sebesar 71,36 dan kelas kontrol rata-rata sebesar 47,72. Hasil belajar yang telah diberikan peserta didik menunjukkan adanya peningkatan pada pengembangan media yang telah diimplementasikan. Media yang telah dikembangkan telah memenuhi syarat kelayakan dengan persentase 83% oleh para validator meskipun begitu peneliti berharap untuk pengembang setelahnya dapat mengembangkan lebih baik lagi dan lebih efektif lagi dalam menganalisis kebutuhan, membuat isi materi , merancang desain dan mengalokasikan waktu pembelajaran dengan tepat.